Effcet of ripening stage on the solar drying kinetics and properties of S. Bartolomeu pears (Pirus Communis L.). - Guiné, Raquel (2013)
Pears of the variety S. Bartolomeu (Pyrus communis L.) have been used over the years in Portugal to produce a traditional dried pear known as “pera passa”. The processing comprehends a solar drying performed at open air, with obvious disadvantages, either concerning the drying efficiency or the sanitary quality of the final product, taking into account that the products are exposed to multiple contamination agents. For these reasons, attempts have been made to study alternative production methodologies, including the use of solar stoves, among others. In the present work pears of the variety S. Bartolomeu (Pyrus communis L.), harvested at three different moments, corresponding to three ripening stages, were dried in a solar stove and their drying kinetics were studied, and the evolution of some properties was monitored along the drying process. From the results obtained it was possible to conclude that the equations used to model the drying kinetics fit with accuracy the experimental data, and that the climatic conditions that occurred in each drying period influenced the drying rate, being essay one clearly faster than the other two essays. On the other hand, considering the evolution of the properties of the pears along drying, it was possible to observe that the pears harvested in the two first dates showed quite similar trends through drying, while the pears harvested at the last date revealed a clear distinct behavior, allowing to deduce that the ripening stage at harvest plays an important role in the drying process.